1999
DOI: 10.1590/s0103-50531999000200004
|View full text |Cite
|
Sign up to set email alerts
|

Photoacoustic Monitoring of Internal Plastification in Poly(3-hydroxybutyrate-co-3-hydroxyvalerate) Copolymers: Measurements of Thermal Parameters

Abstract: Propriedades termofísicas de copolímeros poli(3-hidroxibutirato-co-3-hidroxivalerato) poli(3HB-co-3HV) foram investigadas com o objetivo de entender a influência das unidades monoméricas de 3-hidroxivalerato (3HV) incorporadas durante a copolimerização aleatória. Os resultados mostram forte evidência de que uma plastificação interna é introduzida no copolímero pelas unidades de 3HV. Foi observado que a condutividade térmica do copolímero aumentou linearmente com a concentração de 3HV. Por outro lado, a difusiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 14 publications
0
5
1
1
Order By: Relevance
“…2 /s. These values are slightly higher than those reported by previous authors, 21 who also observed the tendency for saturation of thermal diffusivity. The differences can be attributed to the sample preparation procedure.…”
contrasting
confidence: 70%
“…2 /s. These values are slightly higher than those reported by previous authors, 21 who also observed the tendency for saturation of thermal diffusivity. The differences can be attributed to the sample preparation procedure.…”
contrasting
confidence: 70%
“…Specific thermal capacity of CA/PHB blends was obtained by the photothermal technique through the use of an experimental arrangement composed by an argon laser (Omicron Model 543‐AP) whose beam was modulated with a mechanical chopper (EG&G Model 650). The technique is essentially based on the measurement of temperature fluctuation of a given sample due to the absorption of modulated radiant energy .…”
Section: Methodsmentioning
confidence: 99%
“…The thermocouple monitors the variations of the temperature (Δ T ) with time ( Eq. 2 ) . ΔT=true(I0τlsρCptrue)true(1etτtrue). where I 0 is the intensity of the white light, l s is the film thickness, ρC p is the specific thermal capacity of bulk unit, t is the time.…”
Section: Methodsmentioning
confidence: 99%
“…A copolimerização aleatória de poli(3-hidroxibutirato-co-3-hidroxivalerato) foi estudada desta forma. Além de informações sobre a velocidade de plastificação interna, foram obtidos dados sobre condutividade e difusividade térmica [57] . O número de cadeias poliméricas presentes como partícu-las coloidais é proporcional à quantidade de monômero polimerizado.…”
Section: Outros Métodosunclassified